The Nexus of Climate Adaptation, Public-Private Partnership Investment Flows, and Renewable Energy Transition: Evidence from a Cross-Country Panel Study - Attaqi, Faiz; Komariah, Siti; Pratama, Muhammad I. (Indonesian Journal of Energy, 2026)
What role does climate vulnerability play in directing public-private and private energy investments worldwide? This study investigates the determinants of Public-Private Partnership (PPP) energy investment, private energy investment, and renewable energy output using a random-effects panel data model for 214 countries from 2010-2022. We particularly examine the role of climate vulnerability and readiness, as measured by the ND-GAIN index, alongside institutional, economic, and energy-specific control variables. Our findings reveal that higher climate readiness (lower vulnerability) significantly boosts both PPP and private energy investments. Key institutional factors such as voice and accountability, alongside structural indicators like population and trade openness, also positively influence private energy investment. For renewable energy output, existing renewable energy consumption patterns, foreign direct investment (FDI) inflows, and lower energy intensity (higher efficiency) emerge as significant positive drivers. While direct PPP energy investment does not show a statistically significant direct impact on the share of renewable energy output in our comprehensive models, its role in overall energy sector development, coupled with the crucial influence of climate adaptation capacity, underscores the complex dynamics shaping the global energy landscape. These results highlight the importance of enhancing climate resilience and institutional quality to mobilize necessary capital for a sustainable energy future.